Graphene rubber composites integrated sealing rings for monitoring contact pressure and the aging process. (March 2019) - Yang, Heng; Yao, XueFeng; Zheng, Zhong; Liu, YingHua
Abstract: The graphene rubber composite is a highly sensitive and large-deformation intelligent sensing material, which is used for monitoring the contact pressure and the sealing state of rubber sealing rings. First, the integration of the graphene rubber composites and the sealing rings is achieved through the preform and molding process, which is simple and convenient to operate. Second, the resistance signal of graphene rubber composites related to the contact pressure has good stability and repeatability, which can be used to quantitatively monitor the contact pressure by the developed model. Also, the resistance features of graphene rubber composites integrated sealing rings at different temperatures exhibited high sensitivity and good linearity under compression. Finally, it was found that the resistance signals can also well characterize the artificial aging process of the sealing rings at 120 °C for 72 h, which can provide important information for sealing status and life prediction of O-rings.